Phenotypic and genotypic characterization of levofloxacin- and moxifloxacin-resistant Mycobacterium tuberculosis clinical isolates in southern China - Hameed, H. M. Adnan (J Thorac Dis, 2019)
BACKGROUND: Levofloxacin (LVX) and Moxifloxacin (MXF) are the cornerstones for treatment of multidrug-resistant tuberculosis (MDR-TB). China is one of the highest MDR- and fluoroquinolones (FQ)-resistant TB burdens countries. DNA gyrase encoded by gyr genes is the main target of FQ in Mycobacterium tuberculosis (MTB). The prevalence and molecular characterization of LVX- and MXF-resistant MTB strains from southern China were examined in this study. METHODS: Drug susceptibility testing (DST) of 400 MTB clinical isolates was evaluated by proportion method on Löwenstein-Jensen (LJ) medium against ten drugs. The sequencing of entire gyrA and gyrB genes and multiplex PCR were performed to distinguish the prevalence of mutant types in Beijing and non-Beijing genotypes. RESULTS: Three hundred and twenty-one out of four hundred (80.25%) drug-resistant isolates (resistant > one drug) were categorized as 83/321 (25.80%) MDR, 174/321 (54.20%) pre-XDR and 64/321 (19.93%) XDR-MTB. Overall, 303/400 (75.75%) LVX- and 292/400 (73.00%) MXF-resistant (R) MTB strains were identified. Two hundred seventy-one out of three hundred and three (89.43%) resistant strains carried mutations in gyrA and 91/303 (30.03%) in gyrB. Interestingly, 18 novel mutations were detected in gyrA and gyrB genes. Mutations at (A90, D94) and (T500, G510, G512) frequently existed in QRDR(s) of gyrA and gyrB respectively in 286/400 (71.50%) LVX(R)MXF(R) strains. The novel mutations in- and out-side the QRDR of gyrA (L105R, A126E, M127K, D151T, V165A) and gyrB (D461H, N499S, G520A) increased the sensitivity and consistency of genotypic tests. Notably, 25 LVX(R)MXF(R) strains were found with unknown resistance mechanisms. CONCLUSIONS: Mutations in QRDR(s) were concomitantly associated with Beijing and non-Beijing genotypes. The prevalence of resistance and cross-resistance between LVX and MXF in MTB isolates from southern China was immensely higher than other countries. Our valuable findings provide the substantial implications to improve the reliability of genotypic diagnostic tests relying on potential resistance conferring mutations in entire gyr genes.